2018
DOI: 10.1186/s13007-018-0381-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory chromatin landscape in Arabidopsis thaliana roots uncovered by coupling INTACT and ATAC-seq

Abstract: BackgroundThere is a growing interest in the role of chromatin in acquiring and maintaining cell identity. Despite the ever-growing availability of genome-wide gene expression data, understanding how transcription programs are established and regulated to define cell identity remains a puzzle. An important mechanism of gene regulation is the binding of transcription factors (TFs) to specific DNA sequence motifs across the genome. However, these sequences are hindered by the packaging of DNA to chromatin. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 56 publications
4
42
1
Order By: Relevance
“…The chromatin accessibility regions of A. niger CBS513.88 and SH2 were similarly distributed across the various elements of the genome; the chromatin accessibility regions were found in a high proportion at TSSs (∼70%) and in a low proportion at intergenic regions (∼5%). The proportional distribution of accessible regions is different from what is observed in humans (Ackermann et al 2016), Arabidopsis (Tannenbaum et al 2018) and tomato (Qiu et al 2016), which show a high distribution in intergenic regions and gene bodies. This difference may reflect the smaller size of the A. niger genome (35 Mb) compared with the larger and less compact genomes of humans (750 Mb), Arabidopsis (125 Mb) and tomato (900 Mb).…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…The chromatin accessibility regions of A. niger CBS513.88 and SH2 were similarly distributed across the various elements of the genome; the chromatin accessibility regions were found in a high proportion at TSSs (∼70%) and in a low proportion at intergenic regions (∼5%). The proportional distribution of accessible regions is different from what is observed in humans (Ackermann et al 2016), Arabidopsis (Tannenbaum et al 2018) and tomato (Qiu et al 2016), which show a high distribution in intergenic regions and gene bodies. This difference may reflect the smaller size of the A. niger genome (35 Mb) compared with the larger and less compact genomes of humans (750 Mb), Arabidopsis (125 Mb) and tomato (900 Mb).…”
Section: Discussioncontrasting
confidence: 79%
“…Prior works found that the accessible chromatin regions were positively correlated with gene expression changes of the nearest target genes (Wu et al 2016; Tannenbaum et al 2018; Toenhake et al 2018). We discovered that changing both the culture conditions and deleting TFs can slightly induce differential chromatin accessibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar estimates can be derived for other species and taxa, since nucleosome occupancy and DNA accessibility data are available for all the most widely studied species, as for example in Drosophila (Thomas et al, 2011), or Arabidopsis thaliana (Tannenbaum et al, 2018). In these two species the smaller genome size (hundreds of millions of base pairs) in turn results in a proportionally lower number of estimated accessible regions (tens of thousands).…”
Section: Assessing Statistical Significance Of Peak Overlapsmentioning
confidence: 74%